Regional Expenditure for Sustainable Development: Regional Original Revenue, General Allocation Fund, and Revenue Sharing Fund - Maghfiroh, Anif; Savitri, Dhian Andanarini Minar (E-Jurnal Akuntansi, 2025)
The main objective of this study is to determine the spending patterns of regional original revenue, general allocation fund, and revenue sharing fund by district and city governments in South Sulawesi Province. The research uses a quantitative technique and secondary data from the Regional Revenue and Expenditure Budget Report for 2019-2023 published by the South Sulawesi Provincial Government. Over the time frame of the survey, 21 districts and 3 cities in South Sulawesi Province were included in the population. Multiple linear regression makes use of a descriptive analytic approach, and the data is rigorously analyzed using SPSS software version 27.0, ensuring accurate and reliable results., it was found that local revenue does not influence regional expenditure. On the other hand, the general allocation fund and the revenue sharing fund showed a positive impact on regional expenditure. Keywords: Regional Original Revenue; General Allocation Fund; Revenue Sharing Fund; Regional Expenditure